2010
DOI: 10.1176/appi.neuropsych.22.4.370
|View full text |Cite
|
Sign up to set email alerts
|

Limbic Metabolic Abnormalities in Remote Traumatic Brain Injury and Correlation With Psychiatric Morbidity and Social Functioning

Abstract: The aim of this study was to investigate limbic metabolic abnormalities in remote traumatic brain injury (TBI) and their psychiatric correlates. Twenty patients and 13 age-matched comparison subjects received complete psychiatric evaluation and brain MRI and MR spectroscopy at 3 Tesla. Patients had reduced NAA to creatine ratio in the left hippocampus relative to comparison subjects (mean=1.3 [SD=0.21] compared with mean=1.55 [SD=0.21]; F=10.73, df=1, 30, p=0.003), which correlated with the Social Functioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…Assessment of the relative importance of demographic (age at injury), psychiatric (family history of anxiety disorder, Personality Change due to TBI), and lesion correlates (left IFG, left temporal pole, right frontal white matter lesions, left parietal lesions) were instructive. In adults with TBI, abnormal magnetic resonance spectroscopy findings in left temporal and cingulate areas are related to mood disorder (Capizzano et al, 2010). It is likely that disturbance of critical limbic areas and their relationship to emotional control underlie important neuropathological determinants in the development of post‐TBI depression (Maller et al, 2010), especially given the commonness of frontotemperolimbic damage in pediatric TBI (Bigler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the relative importance of demographic (age at injury), psychiatric (family history of anxiety disorder, Personality Change due to TBI), and lesion correlates (left IFG, left temporal pole, right frontal white matter lesions, left parietal lesions) were instructive. In adults with TBI, abnormal magnetic resonance spectroscopy findings in left temporal and cingulate areas are related to mood disorder (Capizzano et al, 2010). It is likely that disturbance of critical limbic areas and their relationship to emotional control underlie important neuropathological determinants in the development of post‐TBI depression (Maller et al, 2010), especially given the commonness of frontotemperolimbic damage in pediatric TBI (Bigler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, preinjury resiliencies in such neural systems may have protective influences. Based on a model like this, Capizzano et al (2010) speculate on how pre-and post-TBI factors relate to psychiatric morbidity following injury.…”
Section: Premorbid Neurologic and Neuropsychiatric Burden And Cogniti...mentioning
confidence: 99%
“…Metabolites detected through 1 H-MRS provide the necessary information relating to brain injury, inflammation, hypoxia/ischemia and bioenergetic dysfunction. 9 The available literature indicates that extensive study has been performed on hippocampal metabolic irregularities using in vivo 1 H-MRS after moTBI in humans 10 and rodents; 11 however, there is a scarcity of reports on miTBI. Although studies on human miTBI have shown metabolic irregularities in lateral ventricle, splenium 12 and frontal lobe, 13 there has been no in vivo hippocampal MRS study on experimental miTBI.…”
mentioning
confidence: 99%